Final common pathway for tinnitus: theoretical and clinical implications of neuroanatomical substrates. - Shulman, Abraham; Goldstein, Barbara; Strashun, Arnold M. (International Tinnitus Journal, 2009)
A final common pathway (FCP) for tinnitus has been hypothesized since 1989 for all clinical types of tinnitus, particularly subjective idiopathic tinnitus (SIT) of the severe disabling type. This was intended to explain the transformation-transition of the sensation of an aberrant auditory sensation-tinnitus (i.e., the sensory component)-to one of affect (i.e., the emotional-behavioral component) or, conversely, that an emotional-behavioral stimulus (affect) can result in the clinical manifestation of a sensation (a sensory stimulus). Understanding the pathophysiology of this transformation is fundamental for the diagnosis of tinnitus and the treatment of the patient, and it presents a dilemma to basic science, neuroscience, and clinical medicine. Clinically, tinnitus is not a unitary symptom; it constitutes many clinical types; can have its origin in the auditory or nonauditory systems and in the peripheral or central nervous system; and may be clinically manifest or subclinical. Accumulating evidence is presented to support the original hypothesis of an FCP. The resolution of this dilemma involves sensory processing (i.e., the integration, identification, and understanding of the ongoing, underlying, simultaneous, multiple associated brain function processes not only from one sensory modality but from multiple sensory modalities accompanying and associated with an FCP). In the FCP, the predominant brain function process is that of the sensory-affect transformation of a sensation and its conscious awareness by the affected patient. The neuroanatomical substrates identified in 1989 in tinnitus patients (reported originally in 1991 and published in 1995) are presented as a common framework for the hypothesis of an FCP. They further the understanding of the clinical heterogeneity of the tinnitus symptom, clinically manifest as multiple brain functions associated with the clinical course of tinnitus patients, particularly those with SIT. The FCP provides a model for tinnitus theory, diagnosis, and treatment. The FCP is not a tinnitus theory. Specifically, it is a hypothesis that attempts to explain how an aberrant auditory sensory stimulus becomes transformed into one of affect and somatomotor response. The neuroanatomical substrates of the FCP provide a basis for the identification of the involved neurocircuitries and neurochemistries. The physiology and biochemistry underlying the neuroanatomical substrates of the FCP provide a basis for translation for tinnitus diagnosis and treatment. The neuroanatomical substrates of the FCP are presented as algorithms of (1) components of a sensation (i.e., sensory, affect, and psychomotor), a translation from basic sensory physiology for tinnitus; (2) clinically manifest biophysiological brain functions and underlying processes associated with the tinnitus; (3) a model for investigation of metabolic-electrophysiological correlates for tinnitus; (4) the basis for an integrated theory of tinnitus and brain function (i.e., tinnitus dyssynchrony-synchrony theory; (5) a model for the identification of underlying neurocircuitries and neurochemistries involved in brain for the sensory-affect transformation of an aberrant auditory stimulus (tinnitus); (6) a model for the selection-introduction of innovative therapies attempting tinnitus relief; and (7) its clinical translation for objective monitoring systems for the determination of the efficacy of modalities of therapy attempting tinnitus relief. The hypothesis of the FCP for tinnitus and the identified neuroanatomical substrates, when viewed in terms of the physiology of sensory processing, is considered to be expanded and broader in its application for all sensations, normal or aberrant.